2014
DOI: 10.1037/a0035237
|View full text |Cite
|
Sign up to set email alerts
|

Judgments of subtle facial expressions of emotion.

Abstract: Most studies on judgments of facial expressions of emotion have primarily utilized prototypical, high-intensity expressions. This paper examines judgments of subtle facial expressions of emotion, including not only low-intensity versions of full-face prototypes but also variants of those prototypes. A dynamic paradigm was used in which observers were shown a neutral expression followed by the target expression to judge, and then the neutral expression again, allowing for a simulation of the emergence of the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 55 publications
2
31
0
Order By: Relevance
“…However, the forced simultaneous changes of facial features that come with morphing pose a limitation for application in facial emotion recognition experiments. The naturalness of computer-generated expressions is questionable, as it is unclear whether the created movements are anatomically feasible [ 36 , 43 ]. This concerns the onsets of single facial action units, which can vary [ 44 ], and the speed of those action units in reaching apex, which varies between emotions (Hara and Kobayashi as cited by [ 45 ]).…”
Section: Introductionmentioning
confidence: 99%
“…However, the forced simultaneous changes of facial features that come with morphing pose a limitation for application in facial emotion recognition experiments. The naturalness of computer-generated expressions is questionable, as it is unclear whether the created movements are anatomically feasible [ 36 , 43 ]. This concerns the onsets of single facial action units, which can vary [ 44 ], and the speed of those action units in reaching apex, which varies between emotions (Hara and Kobayashi as cited by [ 45 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, [96] found an effect of age on smiling dynamics. Evidence is mixed on whether the AU6 can serve as a "reliable" muscle which is an inevitable sign of enjoyment as compared to posed smiles (AU6 also occurs in posed DDs [11] [17]), but it was shown that the action of the AU6 plays an important role in the perception of spontaneity, authenticity, genuineness of smiles and judgment accuracy [30] [31] [32] [33]. 2 [15] [19] [25] [34] defined the basis of joyful laughter (Duchenne laughter) to consist of a DD plus an audible, laughter-related vocalization and open mouth.…”
Section: Laughter and Smiling In Positive Emotionsmentioning
confidence: 99%
“…In our everyday interactions with others the facial displays of emotion that we encounter are dynamic and most people readily recognise a wide range of affective states, even from very slight and nuanced muscular contractions of the face (Matsumoto & Hwang, 2014). Despite this, much of the research into facial emotion recognition has relied on static photographs of posed expressions.…”
Section: Introductionmentioning
confidence: 99%